Roles of intercellular cell adhesion molecule-1 (ICAM-1) in colorectal cancer: expression, functions, prognosis, tumorigenesis, polymorphisms and therapeutic implications - Qiu, Zhiyuan; Wang, Yan; Zhang, Zhao; Qin, Rong; Peng, Yong; Tang, Weifeng; Xi, Yan; Tian, Guangyu; Zhang, Yeqing (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is a major global health problem and one of the major causes of cancer-related death worldwide. It is very important to understand the pathogenesis of CRC for early diagnosis, prevention strategies and identification of new therapeutic targets. Intercellular adhesion molecule-1 (ICAM-1, CD54) displays an important role in the the pathogenesis of CRC. It is a cell surface glycoprotein of the immunoglobulin (Ig) superfamily and plays an essential role in cell-cell, cell-extracellular matrix interaction, cell signaling and immune process. It is also expressed by tumor cells and modulates their functions, including apoptosis, cell motility, invasion and angiogenesis. The interaction between ICAM-1 and its ligand may facilitate adhesion of tumor cells to the vascular endothelium and subsequently in the promotion of metastasis. ICAM-1 expression determines malignant potential of cancer. In this review, we will discuss the expression, function, prognosis, tumorigenesis, polymorphisms and therapeutic implications of ICAM-1 in CRC.